पौरस्त्य अनुसन्धान दर्शनको रूपरेखा - Gyawali, Hare Krishna (Haimaprabha, 2026)
Evidence of research methods and methodologies is extensively discussed within the literature of Eastern philosophy. These texts explore the quest for knowledge and the process of its validation, alongside various practical aspects of investigation. According to Eastern philosophy, research falls within the domain of the Prāmatā (the researcher/knower), Pramāṇa (the means of knowledge), Prameya (the object of knowledge), and Pramiti (the resulting valid knowledge). The Nyāya-Vaisheshika and Mimamsa schools discuss these four elements in their own unique ways, clarifying how knowledge is sought and validated, as well as the specific procedures and methodologies of inquiry. In Vaisheshika philosophy, the metaphysics of the subject of study is analyzed through seven categories (Padārthas): substance, quality, action, generality, particularity, inherence, and non-existence. Conversely, in Nyāya philosophy, the acquisition of knowledge begins with curiosity (Jigyasa) and is completed once proven through evidence and logical methods. These tools for knowledge validation are detailed across sixteen categories, which serve as the building blocks for knowledge construction and logical reasoning. Furthermore, in Vedanta philosophy, the Anubandha Chatushtaya (qualification, subject matter, relationship, and purpose) and the Shadvidha Linga (six signs) provide frameworks for evaluating research proposals and the axiology of realized knowledge. While these components of research philosophy are highlighted across Eastern literary traditions, there is a lack of integrated study analyzing them collectively as a theoretical framework for Eastern research. This study aims to fill that academic void. To achieve this, data was collected from philosophical texts to draw conclusions. Utilizing a qualitative research design and purposive sampling, information was gathered from three primary sources and several secondary sources. The findings were reached through a descriptive logical analysis of the evidence. Based on this analysis, the study concludes that Eastern philosophical literature provides a clear and systematic outline for the metaphysics, epistemology, and axiology of research philosophy.